An Analysis of Reading Performances of Indonesian EFL Learners for Extensive Reading Practice - Delfi, Syofia; Yamat, Hamidah (Journal of Educational Sciences, 2017)
Learners’ reading performances are needed to be studied in orderto clarify the appropriate context of studies about learners’ extensive readingexperiences.   This article is based on a preliminary study on “a Case Studyon Two Indonesian Learners’ Extensive Reading in English Experiencestowards Developing Reading Competency”.  This article aimed to answertwo questions: (1) How is The Indonesian EFL learners’ readingperformance before learning extensive reading? (2) How is The IndonesianEFL learners’ reading TOEFL score for reading section before learningextensive reading? An analysis was conducted for the data on the documentsof reading performance and Reading Section of TOEFL score. The result ofthis study found: (1) The Indonesian EFL learners’ reading performancebefore learning extensive reading is in the range 66-80 (B) in Reading III forall learners (100%) (2) The Indonesian EFL learners’ TOEFL score forReading section before learning extensive reading is in the range 51% - 80%. These preliminary data were needed in order to indentify the learners’reading performances, therefore, it is expected that the findings aremeaningful for the study designed.